Loss of T cell tolerance in the skin following immunopathology is linked to failed restoration of the dermal niche by recruited macrophages - Heather C. West; James Davies; Stephen Henderson; Oluyori K. Adegun; Sophie Ward; Ivana R. Ferrer; Chanidapa A. Tye; Andres F. Vallejo; Laura Jardine; Matthew Collin; Marta E. Polak; Clare L. Bennett (Cell Reports, 2022)
Summary: T cell pathology in the skin leads to monocyte influx, but we have little understanding of the fate of recruited cells within the diseased niche, or the long-term impact on cutaneous immune homeostasis. By combining a murine model of acute graft-versus-host disease (aGVHD) with analysis of patient samples, we demonstrate that pathology initiates dermis-specific macrophage differentiation and show that aGVHD-primed macrophages continue to dominate the dermal compartment at the relative expense of quiescent MHCIIint cells. Exposure of the altered dermal niche to topical haptens after disease resolution results in hyper-activation of regulatory T cells (Treg), but local breakdown in tolerance. Disease-imprinted macrophages express increased IL-1β and are predicted to elicit altered TNF superfamily interactions with cutaneous Treg, and we demonstrate the direct loss of T cell regulation within the resolved skin. Thus, T cell pathology leaves an immunological scar in the skin marked by failure to re-set immune homeostasis.